ASSESSMENT OF FAMILY AWARENESS IN SAUDI ARABIA REGARDING THE MONKEYPOX VIRUS (CAHIERS MAGELLANES-NS, 2024)
Background: Monkeypox, caused by the monkeypox virus (MPXV), is a zoonotic disease belonging to the Orthopoxvirus genus, related to the smallpox virus family. Although not typically lethal, the disease presents with symptoms such as fever, malaise, headache, back pain, and a characteristic vesiculopustular rash. Initially confined to West and Central Africa, monkeypox has now spread globally, with increased human-to-human transmission. Despite approved medications like the Modified Vaccinia Ankara-Bavarian Nordic (MVA-BN) and tecovirimat, no specific vaccine or treatment for monkeypox exists. Cross-protection from smallpox vaccination is limited in older adults, and younger populations in non-endemic areas have lower immunity. Objective: Our study was designed to assess the awareness of families regarding the monkeypox virus. Methods: This study employed a cross-sectional observational survey conducted among the general Saudi population between September 4, 2024, and October 4, 2024. Participants included Saudi families with at least one child, aged over 18 years, recruited through social media platforms. A sample size of 384 participants was determined using the Qualtrics calculator with a 95% confidence level and a 5% margin of error. Data was collected via an anonymous online questionnaire, which consisted of two sections. The first section gathered sociodemographic information, while the second section included 24 multiple-choice questions assessing participants' knowledge of the monkeypox virus. Informed consent was obtained from all respondents prior to participation. Awareness scores ranged from 0 to 45 points and were categorized into three levels: low (0-15), moderate (16-30), and high (31-45). A pilot test involving 20 individuals was conducted to evaluate the clarity and feasibility of the survey. The data was entered into Microsoft Excel and analyzed using SPSS version 20. Results: Regarding family awareness about the monkeypox virus, 90.5% out of 696 participants have heard of the virus. The internet is the primary source of information for 53.9% of respondents. Participants generally understood common symptoms but 25% were unaware of them. Regarding prevention, 83.6% recognized the need to avoid contact with infected individuals, but only 11.9% felt confident about vaccine accessibility. While 53.9% believe hygiene is effective in prevention, 25.6% are uncertain. Alarmingly, 53.0% are unaware of recent outbreaks, and 36.4% show little concern about its spread. Many (68.2%) think educational institutions should boost awareness, and 58.5% feel media coverage is insufficient. Conclusively, 49.9% of respondents have moderate awareness, while 41.1% exhibit high awareness. Only 9.1% showed low awareness. Conclusion: the study revealed a significant level of awareness concerning monkeypox among families in Saudi Arabia, with 90.5% of participants familiar with the virus. However, there remains a concerning disparity between general awareness and comprehensive understanding, as evidenced by the 25% of respondents unaware of its common symptoms and only 11.9% confident in vaccine accessibility. While a majority acknowledge the importance of preventive measures, a substantial proportion express uncertainty about hygiene effectiveness and perceive inadequate media coverage on the issue.